2013
DOI: 10.1002/bit.25099
|View full text |Cite
|
Sign up to set email alerts
|

A surface‐tethered spheroid model for functional evaluation of 3T3‐L1 adipocytes

Abstract: In order to effectively treat obesity, it must be better understood at the cellular level with respect to metabolic state and environmental stress. However, current two-dimensional (2D) in vitro cell culture methods do not represent the in vivo adipose tissue appropriately due to the absence of complex architecture and cellular signaling. Conversely, 3D in vitro cultures have been reported to have optimal results mimicking the adipose tissue in vivo. The main aim of this study was to examine the efficacy of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(75 citation statements)
references
References 37 publications
3
66
1
Order By: Relevance
“…Attributing 0% conversion to the neat ELP fluorescence and 100% conversion to the neat PEI fluorescence, we calculated the conversion for the ELP-PEI conjugation reaction to be 15 mol%, with the remaining 85 mol% material being the unreacted ELP. Based on our previous research which showed a 5 mol% ELP-PEI solution induced uniform spheroid formation [20,21], we further diluted the reaction product solution with more ELP to obtain a 5 mol% ELP-PEI solution with the remaining 95% material being neat ELP. As shown in Figure 1b, the turbidity of the ELP solution increased due to coacervation as the solution was heated and exhibited an inverse phase transition temperature (T t ) at 37.6 ± 0.9 °C (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Attributing 0% conversion to the neat ELP fluorescence and 100% conversion to the neat PEI fluorescence, we calculated the conversion for the ELP-PEI conjugation reaction to be 15 mol%, with the remaining 85 mol% material being the unreacted ELP. Based on our previous research which showed a 5 mol% ELP-PEI solution induced uniform spheroid formation [20,21], we further diluted the reaction product solution with more ELP to obtain a 5 mol% ELP-PEI solution with the remaining 95% material being neat ELP. As shown in Figure 1b, the turbidity of the ELP solution increased due to coacervation as the solution was heated and exhibited an inverse phase transition temperature (T t ) at 37.6 ± 0.9 °C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For this research, we used discarded adipose tissue from a patient undergoing elective abdominoplasty or liposuction to study the impact of 3-D spheroid culturing technique on primary stromal vascular preadipocyte (hASC) differentiation and overall functionality. hASCs were cultured using similar methods pioneered with H35 rat hepatoma and 3T3-L1 preadipocyte model cells [20,21], though using maintenance media optimized for hASCs [26,32]. The experimental timeline is shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to 2D culture, 3D culture for adipogenesis in general could: 1) deposit an extensive ECM network (Grayson et al, 2004), 2) recapitulate adipose stem cell microenvironments (Yang et al, 2010), 3) enhance adipogenic differentiation, exhibiting more mature adipogenesis of stem cells (Gerlach et al, 2012), efficient lipid accumulation and in vivo-like organogenesis (Daquinag et al, 2013), expression of adipocyte-specific markers (Hong et al, 2005; Neubauer et al, 2005; Stacey et al, 2009) as well as VEGF (Girandon et al, 2011), and increase secretion of adipokines such as leptin (Kang et al, 2005), 4) be more sensitive to insulin-stimulated glucose uptake and drug treatment (Brännmark et al, 2014; Turner et al, 2014), 5) allow long-term survival (Neuss et al, 2008a), and 6) be feasible to manipulate cellular microenvironments for adipogenesis (Daya et al, 2007). …”
Section: 3d Microenvironments To Control Adipogenesis Of Stem Cellsmentioning
confidence: 99%